The Relationship between Knowledge and Adolescents' Attitudes toward Early Marriage in Sekardadi Village, Kintamani District, Bangli Regency In 2025 - Erni, Ni Nengah Budi; Senjaya, Asep Arifin; Utarini, Gusti Ayu Eka (Jurnal Midwifery, 2026)
Introduction Based on the National Socio-Economic Survey (SUSENAS) 2023, around 33,74% of Indonesian women aged 20–24 years old have been married before the age of 19, and around 11.21% got married before the age of 18. This study aims to determine the relationship between knowledge and attitudes of adolescents about early marriage in Sekardadi Village, Bangli Regency in 2025. This research method uses a correlation analytic design with a cross-sectional approach. A sample of 70 respondents, namely all adolescents aged 11-20 years who are registered as residents in Sekardadi Village, Kintamani District, Bangli Regency in 2025, was taken using the total sampling method. Data were collected using a questionnaire and analyzed using the chi-square test with statistical test results indicating that there is a significant relationship between the level of knowledge and attitudes of adolescent girls towards early marriage with a value of χ² = 22.657 and a significance level of p = 0.000 (p <0.05). As many as 87.1% of respondents are in the good knowledge category and as many as 98.6% of adolescent girls have a positive attitude towards the issue of early marriage. Conclusion so that there is a significant relationship between the level of knowledge and the attitude of young women towards early marriage. Suggestions for the village to continue and strengthen educational efforts through ongoing counseling programs for teenagers, in order to encourage them to delay the age of marriage.